The annoying crush - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack ;, 2014)
Zack is happy to test a new android his father helped develop for Nebulonics before she goes into production, but her ability to learn causes problems when she develops a crush on Zack after watching a romantic movie.